A 100% Aqueous Mobile Phase HPLC-photodiode Array Detection of Tetracycline and Its 4-epimer, 4-epi-tetracycline - Furusawa, Naoto (Current Advances in Chemistry and Biochemistry Vol. 9, 2021)
This paper introduces an organic solvent-free mobile phase HPLC system for simultaneous analysis of tetracycline (TC) and 4-epi-tetracycline (4eTC). The chromatographic separation was achieved an Inertsil® WP300 C4 column with an isocratic aqueous mobile phase and a photodiode array detector (PAD). The run-time was < 5 min/sample. The main validation performance parameters, linearity, range, and system suitability, were well within the international recommended criteria. The detection limits for TC and 4eTC were 0.005 and 0.014 \(μ\)g/mL, respectively. The high repeatable, quick, and easy HPLC-PAD system may be further effective for the quantifying TC and 4eTC residues in animal-derived foods.